2022
DOI: 10.1038/s41467-022-32573-w
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous humoral and cellular immune responses with distinct trajectories post-SARS-CoV-2 infection in a population-based cohort

Abstract: To better understand the development of SARS-CoV-2-specific immunity over time, a detailed evaluation of humoral and cellular responses is required. Here, we characterize anti-Spike (S) IgA and IgG in a representative population-based cohort of 431 SARS-CoV-2-infected individuals up to 217 days after diagnosis, demonstrating that 85% develop and maintain anti-S responses. In a subsample of 64 participants, we further assess anti-Nucleocapsid (N) IgG, neutralizing antibody activity, and T cell responses to Memb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 72 publications
6
24
0
Order By: Relevance
“…We then estimated the half-life of the decrease of the antibody titer directly from the seroprevalence data, using an extension of the classic Susceptible-Exposed-Infectious-Removed (SEIR) model 26 . Assuming an average time to seroconversion of 14 days 27-29 , an average generation interval of 5.2 days 30 and an average time from disease onset to death of 20.2 days 31 , the overall half-life observed on the level of the population is 75 (CrI95% 55-103) days (unadjusted) or 88 (CrI95%: 61-128) days (post-stratification for age and sex), similar to what was reported by others 32 . We then computed the cumulative incidence of CoV2, i.e.…”
Section: Antibody Waning and Cumulative Incidencesupporting
confidence: 87%
See 2 more Smart Citations
“…We then estimated the half-life of the decrease of the antibody titer directly from the seroprevalence data, using an extension of the classic Susceptible-Exposed-Infectious-Removed (SEIR) model 26 . Assuming an average time to seroconversion of 14 days 27-29 , an average generation interval of 5.2 days 30 and an average time from disease onset to death of 20.2 days 31 , the overall half-life observed on the level of the population is 75 (CrI95% 55-103) days (unadjusted) or 88 (CrI95%: 61-128) days (post-stratification for age and sex), similar to what was reported by others 32 . We then computed the cumulative incidence of CoV2, i.e.…”
Section: Antibody Waning and Cumulative Incidencesupporting
confidence: 87%
“…If antibody titers were stable after infection, the seroprevalence would reflect the entirety of the population infected since inception of the pandemic. However, anti-CoV2 titers were found to decay in multiple studies [11][12][13][14][15]32 , with a half-life of approximately 106 (CI95% 89 to 132) days 11 , 76 to 156 days 32 , and others suggesting an even shorter half-life of 26 to 60 days 13 . This decrease in titers over time was confirmed in neutralization assays, shown in various studies 12,14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of vaccine antigen to the draining LNs is crucial for the initiation of systemic immune responses against the relevant pathogen by T and B cells ( 23 ). Previous studies have indicated that protective immunity against COVID-19 is mediated by both key arms of the adaptive immune system, i.e., humoral immunity and cellular immunity ( 34 37 ), and that antibody and T-cell responses tend to work in a compensatory manner to provide protection ( 38 ). Humoral immunity generates antibodies and memory B cells, while cellular immunity leads to the activation of antigen-specific helper CD4 + T cells and cytotoxic CD8 + T cells ( 13 ), which both occur in the draining LNs ( 39 , 40 ).…”
Section: Covid-19 Mrna Vaccines Activate Adaptive Immunity In the Dra...mentioning
confidence: 99%
“…There is wide, largely unexplained heterogeneity in immunological and clinical responses to SARS-CoV-2 infection ( Karachaliou et al, 2021 ; Menges et al, 2022 ; Le Bert et al, 2021 ; Mazzoni et al, 2021 ). Personal characteristics, comorbidities, lifestyles, living conditions, and the shared environment only partly account for such variation; this is particularly clear among healthy individuals from the general population ( Kogevinas et al, 2021 ; Weaver et al, 2022 ; Patanavanich and Glantz, 2021 ).…”
Section: Introductionmentioning
confidence: 99%